Competition and the Number of Firms in a Market: Are Duopolies More Competitive than Atomistic Markets? - Stiglitz, Joseph E. (Journal of Political Economy, 1987)
This paper uses a variant of the standard search model to examine market equilibrium and the consequences of an increase in the number of firms. If marginal search costs increase with the number of searches, then the demand curve facing any firm will be kinked, with the elasticity of demand with respect to price decreases being less than with respect to price increases; prices may not change in response to changes in marginal costs. As the number of firms increases, the maximum price that is consistent with equilibrium increases to the monopoly price, but the minimum price decreases. On the other hand, if marginal search costs decrease with the number of searches, equilibrium, if it exists, is characterized by a price distribution.